From being a Eunuch (Hijra) to a Third Gender in India: a Socio-Legal Study on Gender Disability of Eunuchs - Chatterjee, Dr. Pyali (Medicine, Law & Society, 2022)
This paper will focus on the inequalities faced by the third gender (hijras) in India due to their disability, which is not even considered under The Persons with Disabilities (Equal Opportunities, Protection of Rights and Full Participation) Act, 1995. Their Disability is the core reason that people from third gender have faced discrimination in society since the British period. This paper also traces the transition phase of the third-gender in Indian history from being a hijra to a criminal and then to a thirdgender. A primary aim of this paper is to discuss the disability of the third gender which is the main cause of the plight being faced by them even presently. The researcher also highlights the fact that the disability faced by hijras is different from the physical and/or mental disability described in the Disability Act of India, and therefore, their medical conditions must be included in the Disability Act. The article concludes with a series of concrete steps that the Indian government should take to help ensure that the hijras are brought back into the mainstream of the society and to help obviate their longterm suffering and humiliation.